Veterans' Use of Veterans Health Administration Primary Care in an Era of Expanding Choice. Issue 6 (June 2021) - Hynes, Denise M.; Edwards, Samuel; Hickok, Alex; Niederhausen, Meike; Weaver, Frances M.; Tarlov, Elizabeth; Gordon, Howard; Jacob, Reside L.; Bartle, Brian; O'Neill, Allison; Young, Rebecca; Laliberte, Avery
Abstract : Background: The Veterans Choice Program (VCP), aimed at improving access to care, included expanded options for Veterans to receive primary care through community providers. Objectives: The objective of this study was to characterize and compare Veterans use of Veterans Health Administration (VA) primary care services at VA facilities and through a VA community care network (VA-CCN) provider. Research Design: This was a retrospective, observational over fiscal years (FY) 2015–2018. Subjects: Veterans receiving primary care services paid for by the VA. Measures: Veteran demographic, socioeconomic and clinical factors and use of VA primary care services under the VCP each year. Results: There were 6.3 million Veterans with >54 million VA primary care visits, predominantly (98.5% of visits) at VA facility. The proportion of VA-CCN visits increased in absolute terms from 0.7% in 2015 to 2.6% in 2018. Among Veterans with any VA-CCN primary care, the proportion of VA-CCN visits increased from 22.6% to 55.3%. Logistic regression indicated that Veterans who were female, lived in rural areas, had a driving distance >40 miles, had health insurance or had a psychiatric/depression condition were more likely to receive VA-CCN primary care. Veterans who were older, identified as Black race, required to pay VA copayments, or had a higher Nosos score, were less likely to receive VA-CCN primary care. Conclusion: As the VA transitions from the VCP to MISSION and VA facilities gain experience under the new contracts, attention to factors that impact Veterans' use of primary care services in different settings are important to monitor to identify access barriers and to ensure Veterans' health care needs are met.